Védett növényfajok együttes előfordulása szárazgyepekben - Csontos, Péter; Isépy, István; Tamás, Júlia; Lőkös, László (TÁJÖKOLÓGIAI LAPOK, 2007)
The paper discusses co-existence of protected plant species growing in dry grasslands of the Carpathian Basin. Our approach is based on a hypothesis that the presence of a rare, protected species on a habitat can be considered as indicator for potential presence of some further rare species (having similar ecological requirements). Based on this „indicator hypothesis” we also believe that the given habitat can successfully support transplanted populations of the indicated species. So thus, this approach can be used for nature conservation operations, when species from threatened habitats need to be transplanted into a safe place. For demonstration purposes, the paper shows examples for co-existence of protected species at three different spatial scales, as follows: at landscape scale, at the scale of a 250 m by 250 m grid system survey and at the level of phytosociological relevés. In each case realised rates of co-existences and predicted rates of co- existences were compared (based on occurrence probabilities of individual protected species). Altogether, values related to 41 species pairs are listed in tables. Advantages and limitations of the proposed method are discussed.
Keywords: cönológiai lépték; előfordulási valószínűség; koegzisztencia; szárazgyepek; sziklagyepek; táji lépték; védett növények